Analisa Laporan Keuangan Nasabah dan Peranannya dalam Pemberian Kredit pada PT Bank Rakyat Indonesia (Persero) Tbk Unit Lubuk Begalung Padang - Bennyman Ilham Dani Isni; Febryandhie Ananda (Universitas 45 Surabaya, 2024)
Financial reports have a dual role as a guide for customers in preparing financial reports and as a source of inspiration for BRI's credit department. Analysis of customer financial reports, supported by financial reports, becomes an integral part of the credit process. Research involves credit monitoring procedures and analysis of customer financial reports. Case studies on Toko Rhio Yudha Gama and Toko Dikcy Oksani Junaidi show positive results in liquidity, solvency and profitability, validating their suitability for obtaining credit with low risk. Analysis of financial ratios, such as current ratio, quick ratio, debt to total asset ratio, and return on equity, provide a satisfactory performance picture. The research conclusion confirms that credit assessment based on analysis of financial statements and profit and loss has great significance. Financial ratios are the main indicator, reflecting whether a customer is worthy of receiving a loan. In addition, BRI Bank determines the loan nominal using Repayment Capacity, which is the customer's repayment capacity of 50% of the net profit in the profit and loss statement.